Fraud Research in Economic Entities – A Conceptual Perspective - Alexandru Adrian TUNSU (Audit Financiar)
In the growing complex and mutualistic context of global economies, addressing the circumstances in which fraud is observed is becoming of fundamental importance. National and global economies are severely affected by fraud by economic entities through significant financial losses, diminished investor confidence and the creation of financial market imbalances. From this perspective, the research objective is to identify and analyse multidimensional conceptual approaches to fraud. Using a bibliometric analysis of articles published in the Scopus database in the period 1982-2023, the research directions in the literature, the frequency and relevance of the topics addressed, the authors and papers with major influence, as well as the collaboration networks among researchers were identified. The results of the research highlighted the continuing interest in addressing fraud but also its multiple connotations. Considering the economic, governmental and social implications of fraud, the research is deemed to add value to the literature and the changing economic context is a premise for further research on fraud.